2013
DOI: 10.1515/gcc-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

On the dimension of matrix representations of finitely generated torsion free nilpotent groups

Abstract: It is well known that any polycyclic group, and hence any finitely generated nilpotent group, can be embedded into GLn(Z) for an appropriate n ∈ N; that is, each element in the group has a unique matrix representation. An algorithm to determine this embedding was presented in [6]. In this paper, we determine the complexity of the crux of the algorithm and the dimension of the matrices produced as well as provide a modification of the algorithm presented in [6].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Up to now there are no bounds known neither on the running time nor on the dimension of the embedding obtained by Nickel's algorithm. In [3], a polynomial bound for both is claimed; however, there is a gap in the proof. Indeed, here we prove these results to be wrong: our main result (Theorem 3.9) establishes the lower bound of N ≥ 2 n/2−2 for the embedding of U T n (Z) (with the standard Mal'cev basis as in Nickel's paper) into U T N (Z) computed by Nickel's algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now there are no bounds known neither on the running time nor on the dimension of the embedding obtained by Nickel's algorithm. In [3], a polynomial bound for both is claimed; however, there is a gap in the proof. Indeed, here we prove these results to be wrong: our main result (Theorem 3.9) establishes the lower bound of N ≥ 2 n/2−2 for the embedding of U T n (Z) (with the standard Mal'cev basis as in Nickel's paper) into U T N (Z) computed by Nickel's algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Graaf and Nickel [14] and Nickel in [33] studied the classical linear representations of finitely generated torsion-free nilpotent groups G into U T n (Z) from the algorithmic view-point, showing in particular that there are polynomial time (in the Hirsh length of G) algorithms to construct the representations. Recently, in [17] Habeeb and Kahrobaei, following [33], showed that the dimension of the classical representations above is O(n 2 ) where n is the Hirsh length of the group. It seems the dimension is not prohibitively high in this case.…”
Section: Introductionmentioning
confidence: 99%